The Relationship Between Adolescents’ Knowledge of Reproductive Health and Their Behavior in Preventing Sexually Transmitted Infections - Cakrawati R Cakrawati R; Nurhayati Nurhayati (International Journal of Health Sciences, 2026)
ABSTRACT Sexually transmitted infections (STIs) remain a significant public health problem among adolescents. Lack of knowledge regarding reproductive health often contributes to risky behaviors that increase the likelihood of STI transmission. This study aimed to determine the relationship between adolescents’ knowledge of reproductive health and their behavior in preventing sexually transmitted infections. This study used a quantitative approach with a descriptive analytic design and a cross-sectional method. The sample consisted of 40 adolescents selected using purposive sampling techniques. Data were collected using questionnaires related to reproductive health knowledge and STI prevention behavior. Data analysis was conducted using univariate analysis and Chi-Square statistical tests. The results showed that most adolescents had a moderate level of reproductive health knowledge. Adolescents with good knowledge tended to demonstrate better preventive behaviors against sexually transmitted infections. Statistical analysis showed a p-value of 0.002 (p < 0.05), indicating a significant relationship between adolescents’ knowledge of reproductive health and their behavior in preventing sexually transmitted infections. In conclusion, adolescents’ knowledge of reproductive health is significantly related to preventive behaviors against sexually transmitted infections. Therefore, health education and reproductive health promotion among adolescents need to be improved to reduce the risk of STI transmission. Keywords: Adolescents, Reproductive Health Knowledge, Sexually Transmitted Infections, Preventive Behavior, Health Education